Pengelolaan Program Talent Class Badminton Sebagai Pengembangan Minat dan Bakat Peserta Didik di Homeschooling Kak Seto Surabaya - Islamey, Reza Almira; Siswanto, Heru (J+PLUS UNESA, 2024)
This research aims to describe the management of the badminton Talent Class program as developing students' interests and talents at the Kak Seto Surabaya Homeschooling , which includes planning, implementation and evaluation. This research uses a phenomenological approach with qualitative research methods. Data collection through observation, interviews and documentation. Data were analyzed using the Miles and Huberman interactive analysis model through several activity procedures, namely data reduction, data presentation and drawing conclusions. The research results show; Developing interests and talents through the Badminton Talent Class starts with choosing a regular class or distance learning, then continues with the counselor to detect academic, family and social background as well as interests and talents. the problems faced by the child or the background of life problems. At the implementation stage, tutors also design learning tools and learning media so that they can achieve their goals. Meanwhile, at the evaluation stage, the results of the learning evaluation are given in graphic form which functions to measure the extent to which students have achieved academic and non-academic abilities. The output of this Badminton Talent Class is that children can develop their own interests in the future. The suggestion from this research is that in accordance with the management of Homeschooling which is full of the content of individual existence, the implementation of Homeschooling must have adequate standardization in identifying students' talents, interests and potential.